ACHIEVEMENT OF STUDENT'S LEARNING OBJECTIVES THROUGH COOPERATION OF SCHOOL PRINCIPLES AND TEACHERS IN MTS PROJECT KANDEPAG MEDAN - Rahmat Hidayat; Murniati Murniati (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
This study aims to find out (1) how the learning objectives of students in the MTS project of the Ministry of Religion Medan, (2) how the efforts to achieve student learning objectives in the MTS project of the Ministry of Religion of Medan, (3) how the cooperation of principals and teachers in efforts to achieve student learning goals at MTS the field office of the ministry of religion project, (4) what are the obstacles faced in achieving the learning objectives in the MTS project of the field office of the ministry of religion. This study uses qualitative. I chose this qualitative approach to gain insight into the achievement of student learning goals through the collaboration of principals in the MTS project, Ministry of Religion, Medan. Data collection techniques in this study, using a list of interviews, documentation, and observation. The subjects in this study were the principal, vice-principal, and teaching staff. The results of the study indicate that learning in the MTS project of the Medan Ministry of Religion has not been well established because there is still a lack of communication between principals and teachers, which is a very necessary role for students. The main factor for good communication is the lack of input from the principal for teachers about the effectiveness of teaching and learning in the classroom. So from this problem, the researcher can conclude that the scope of the teacher who is less involved is very influential on the students in motivating to learn.